2008
DOI: 10.1128/aac.00849-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Activities of the Investigational Fluoroquinolone DC-159a and Other Antimicrobial Agents against Human Mycoplasmas and Ureaplasmas

Abstract: The in vitro susceptibilities of 151 unique clinical isolates of Mycoplasma pneumoniae, Mycoplasma hominis, Mycoplasma fermentans, Mycoplasma genitalium, and Ureaplasma species to DC-159a, an investigational fluoroquinolone, in comparison with those to other agents were determined. Macrolides were the most active agents against M. pneumoniae and M. genitalium, whereas clindamycin was most active against M. hominis. DC-159a MICs were <0.5 g/ml for all Mycoplasma species and <4 g/ml for ureaplasmas. DC-159a was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…These high rates of persistent detection, even among men who denied unprotected sex between visits, contrast with the apparent in vitro susceptibility of UU-2 and UP isolates that we observed. Consistent with our findings, studies examining Ureaplasma susceptibility to azithromycin 19 and moxifloxacin 17 19-21 have generally observed isolates in the susceptible range and have not noted differences in susceptibility patterns by species. However, the universal in vitro susceptibility to doxycycline in this study is in contrast to studies conducted in Europe and West Africa, where 18-37% of Ureaplasma isolates demonstrated in vitro resistance to doxycycline.…”
Section: Discussionsupporting
confidence: 90%
“…These high rates of persistent detection, even among men who denied unprotected sex between visits, contrast with the apparent in vitro susceptibility of UU-2 and UP isolates that we observed. Consistent with our findings, studies examining Ureaplasma susceptibility to azithromycin 19 and moxifloxacin 17 19-21 have generally observed isolates in the susceptible range and have not noted differences in susceptibility patterns by species. However, the universal in vitro susceptibility to doxycycline in this study is in contrast to studies conducted in Europe and West Africa, where 18-37% of Ureaplasma isolates demonstrated in vitro resistance to doxycycline.…”
Section: Discussionsupporting
confidence: 90%
“…There have been no reports of naturally occurring resistance to fluoroquinolones in M. pneumonia to date. In vitro activity against macrolide‐resistant M. pneumoniae isolates has been reported for a number of fluoroquinolones, with MIC 90 s being lower for moxifloxacin (≤0.0008–0.125 µg/mL), garenoxacin (0.016–0.0625 µg/mL) and gatifloxacin (0.016–0.064 µg/mL) than for levofloxacin (0.25–0.5 µg/mL), ciprofloxacin (0.5–4.0 µg/mL) and tosufloxacin (0.25–0.5 µg/mL) . Fluoroquinolones have also proved effective in the treatment of macrolide‐resistant M. pneumoniae infections.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, they are no longer a valid therapeutic option in some areas [ 5 , 7 ]. As no resistance to levofloxacin (or other newer fluoroquinolones) and clindamycin is yet identified, these drugs could be a suitable therapeutic alternative [ 5 , 7 , 20 , 22 , 23 ]. The increasing resistance of M. hominis strains to antibiotics makes guidance of therapy by in vitro susceptibility tests of paramount importance in invasive infections leading to life-threatening situations.…”
Section: Discussionmentioning
confidence: 99%